Assessment of Lift Net Catch Productivity in Tonyaman Village, Polewali Mandar, West Sulawesi - Etika Ariyanti Hidayat; Eka Erliana; Ady Jufri; Muhammad Nur Ihsan; Zulfathri Randhi (Jurnal Perikanan Terpadu, 2026)
Lift net productivity is a key indicator of fishing gear and operational efficiency in Tonyaman. This study aimed to analyze the productivity and species composition of fish catches from two lift net units using experimental fishing, with each unit conducting 15 trips. Data included catch volume per trip and species identification. Results showed fluctuating productivity: Lift net 1 initially declined (1–2 kg/trip) but increased to 6–7 kg/trip, while Lift net 2 showed a significant rise from day 9, reaching up to 15 kg/trip. Species composition varied, with 12 species in net 1 and 10 in net 2. Average productivity was 5.097 kg/trip for net 1 and 6.616 kg/trip for net 2. Catch composition revealed a higher proportion of target species in net 2. To enhance efficiency and yield, it is recommended that fishers adopt fishing technologies and consider seasonal patterns in their operations